So you want to work in a museum? - Young, Tara Reddy (Rowman & Littlefield, 2019)
"This book discusses some of the benefits of working in museums according to size, type, and organizational structure; and goes through dozens of museum positions in detail. It is designed to introduce college students, graduate students, and/or young professionals to the museum field"--